2006
DOI: 10.2135/cropsci2005-0186
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathic Potential of Winter Cereals and Their Cover Crop Mulch Effect on Grass Weed Suppression and Corn Development

Abstract: Field experiments were conducted to study the effect of three rye (Secale cereale L.) populations, six triticale (3Triticosecale Wittm.) cultivars, and two barley (Hordeum vulgare L.) cultivars, used as cover crops, on the emergence and growth of barnyardgrass [Echinochloa crus-galli (L.) P. Beauv.], bristly foxtail [Setaria verticillata (L.) P.Beauv.], and corn (Zea mays L.). Moreover, bioassay studies were conducted to assess allelopathic potential of the winter cereal extracts on both weed species and corn.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
74
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(83 citation statements)
references
References 30 publications
(66 reference statements)
8
74
0
1
Order By: Relevance
“…However, delay in RCC control occurred at some site-years due to wet soil conditions. The intent was also to wait a minimum of 7 d after RCC control to plant corn in an attempt to avoid potential negative effects (Dhima et al, 2006), and plant soybean at or within 7 d after rye control.…”
Section: Experimental Design and Treatment Applicationmentioning
confidence: 99%
See 2 more Smart Citations
“…However, delay in RCC control occurred at some site-years due to wet soil conditions. The intent was also to wait a minimum of 7 d after RCC control to plant corn in an attempt to avoid potential negative effects (Dhima et al, 2006), and plant soybean at or within 7 d after rye control.…”
Section: Experimental Design and Treatment Applicationmentioning
confidence: 99%
“…That was not the case in our study, where reduced yield was potentially due to an allelopathic effect from the RCC on corn growth or differences in soil properties between no-RCC and RCC during the growing season. Also, RCC biomass can create a surface mulch that would change soil moisture and temperature patterns and negatively affect corn growth (Dhima et al, 2006). Waiting only 7 to 10 d for planting corn after RCC control has been reported to be enough to avoid the allelopathic effect of RCC on corn growth (Duiker and Curran, 2005).…”
Section: Corn Yield and Nitrogen Response Corn Yieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional potential benefits from cover crops include improved infiltration, decreased erosion, enhanced microbial biomass, increased weed suppression, and improved C sequestration and soil organic matter (Kaspar et al, 2001;Franzluebbers, 2005;Sainju et al, 2005;Dhima et al, 2006;Hoorman et al, 2009;Olson et al, 2010;Bernstein et al, 2011;Mirsky et al, 2013;Tabaglio et al, 2013;Moore et al, 2014;McDaniel et al, 2014). An issue with cover crops in the upper Midwest, however, is the cold and generally short period for growth between harvest and spring planting of annual crops (Dinnes et al, 2002).…”
mentioning
confidence: 99%
“…Negative RCC effects on corn growth and yield (Johnson et al, 1998;Thelen and Leep, 2002;Kramberger et al, 2009;Pantoja et al, 2015) make farmers reluctant to use an RCC or to allow adequate time to grow in the spring (Tollenaar et al, 1993;Vaughan and Evanylo, 1998;Dinnes et al, 2002;Dhima et al, 2006). Lamarca (1996) found that when accumulated cereal cover crop biomass was less than 3000 kg DM ha -1 , the strongest negative effect on corn growth was for the 4-wk period after cover crop termination; however, greater cover crop biomass resulted in an extended negative effect.…”
mentioning
confidence: 99%